Waste and Risk at the Restricted Food Industry - Abouel Kawaam, Jennah (2025)
The bachelor thesis proposes possible improvements to meat production under halal restrictions from the lean management perspective by implementing FMEA to the Lean Waste in the system. Restricted diets such as kosher, halal, vegetarian, vegan, and gluten-free have moved from niche practices to mainstream consumer markets, creating both opportunities and challenges for global food systems. This industry is heavily embedded in religious law and health requirements, however; they also face different operational risks, including certifications fragmentation and supply chain weaknesses. The methodological framwork is based on Halal Six Sigma (HSS) and the DMAIC cycle, while being supported by lean tools such as SIPOC, flowcharts, FMEA, and Pareto chart. The practical part applies these tools to the case study chosen; processes were mapped, wastes and risks were identified, and quanitified through Risk Priority Numbers (RPNs). TIM WOODS framework was used to categorize wastes, and To reduce RPN and mitigate risks targeted improvements were implemented. The bachelor thesis provides evidence of possible lean waste from a risk analysis perspective in halal meat production. This evidence fills the gap in the existing literature from this perspective and this type of operation. By implementing the Waste Risk Analysis (WRA) in this production process, the bachelor thesis provides insights for operation managers on the risks and possible solutions/improvements.